Analisis Kritis Hadis tentang Nafkah Halal dan Kesalehan Anak: Perspektif Pendidikan Anak dalam Islam - Sabila Azmi Syahira; Suparta; Romlah Abubakar Askar (At Turots: Jurnal Pendidikan Islam, 2026)
This study critically examines the theological and ethical implications of illicit (haram) income on the acceptance of supplication, with particular attention to its consequences for child piety and spiritual development. Employing a qualitative approach grounded in hadith analysis, the research investigates the prophetic tradition narrated by Abu Hurairah in Sahih Muslim concerning the rejected supplication of a traveler whose sustenance derives from forbidden sources. The analysis reveals a strong correlation between the halal status of provision and the efficacy of worship, extending this principle to contemporary cases of parents who pursue unlawful income under the justification of providing for their children. Drawing upon classical jurisprudential sources, modern scholarly interpretations, and empirical data on economic behavior in Muslim-majority societies, the study argues that the pursuit of haram income undermines both the spiritual standing of the provider and the religious formation of dependents. The findings highlight the need to reassess prevalent economic practices within Muslim communities and emphasize that genuine parental responsibility entails not only material provision but also the sanctification of such provision through adherence to Islamic ethical standards. This research contributes to ongoing discourse on Islamic economic ethics and family law by demonstrating that the hadith’s theological warning retains immediate relevance for contemporary Muslim families navigating tensions between economic pressures and religious obligations.